Putusan Mahkamah Konstitusi: Dampaknya terhadap Perubahan Undang-Undang dan Penegakan Hukum Pidana - Nyoman Mas Aryani; Bagus Hermanto (The Constitutional Court of the Republic of Indonesia, 2021)
Constitutional Court verdict have big impact for laws development including criminal law. In criminal law, the verdict caused change in norm both arranged inside Criminal Law Code and outside Criminal Law Code. Futhermore, this issue is interesting to study when it is connected with expansion authority of Constitutional Court from negative legislator to positive legislator. Constitutional Court verdict form as ‘conditional’ verdict either constitutional or conditional inconstitutional are example of the transformed Constitutional Court authority from negative legislator to positive legislator. As known, criminal law is basing on legality principle. Thus, the verdict especially ‘conditional’ verdict raises polemic in its implementation because not all the verdict can be followed by changing criminal law formally. This situation can inflict various difference in criminal law enforcement. Constitutional Court verdict evoke changing criminal law norm by decriminalization, depenalisation, offense transformation or interpretation criminal law elements that impact on material criminal law or formal criminal law. Without any follow up by changing criminal legislation, espesially when it is related with legalty principle, law enforcement officer can rule out Constitutional Court verdict. The inconsistency of law enforcement can provoke law uncertainty and violate citizen rights